Shaping tomorrow: how the STEP training course pioneered noninvasive brain stimulation training for psychiatry in France - Mondino, Marine; Neige, Cécilia; Batail, Jean-Marie; Bouaziz, Noomane; Bubrovszky, Maxime; Bulteau, Samuel; Demina, Anastasia; Dormegny-Jeanjean, Ludovic C.; Harika-Germaneau, Ghina; Januel, Dominique; Laidi, Charles; Moulier, Virginie; et al. (Frontiers in Psychiatry, 2024)
Over the past three decades, non-invasive brain stimulation (NIBS) techniques have gained worldwide attention and demonstrated therapeutic potential in various medical fields, particularly psychiatry. The emergence of these novel techniques has led to an increased need for robust training programs to provide practitioners, whether clinicians or scientists, with the necessary skills and knowledge. In response, a comprehensive training curriculum for NIBS in psychiatry has been developed in France. This curriculum was developed by a group of researchers and psychiatrists interested in the clinical application of NIBS in psychiatry, called STEP - Stimulation Transcranienne en Psychiatrie, under the auspices of the French Association of Biological Psychiatry. This perspective outlines the development and implementation of this course, tracing its inception, the evolution of the program, and the challenges encountered along the way. The position of the course in the national and international environment and its future prospects are also discussed. Through this perspective, we aim to summarize the collaborative efforts to promote NIBS teaching and research in French psychiatry.